The effectiveness of work-life balance practice in the Chinese Internet industry - XIE, ZILIN (2020)
Abstract Work-life balance (WLB) as one of the most indispensable components in retaining human resources plays a more crucial role in almost all organizations. Additionally, numerous previous studies claim that a sustainable and effective WLB practice not only could enhance the gender equality, employment satisfaction and employment flexibility from the perspective of employees but also improve the company loyalty from the perspective of organizations. Hence, this study put these four different factors as criteria to reflect the effectiveness of WLB practice. Apart from that, the Chinese Internet industry as a rapid-developing and emerging field have the characteristic of overtime employment, massive workloads and high working pressure. Meanwhile, the majority of Internet-related practitioners face the challenge of work-life conflicts. Therefore, it is necessary and meaningful to analyze the effectiveness of WLB practice in the Chinese Internet industry. In addition, this study adopts a quantitative research approach, and 161 participants who work in the Chinese Internet industry are conducted in the survey of the online self-completion questionnaire. After summarizing the previous finding and analyzing the collected sample by the software of SPSS, most Chinese Internet practitioners feel satisfied with WLB practice in their workplaces and family. By the same token, this research found that gender equality and employment satisfaction have a positive significant impact on the effectiveness of WLB practice, while employment flexibility and company loyalty do not affect the effectiveness of WLB.